B, As, and F contamination of river water due to wastewater discharge of the Yangbajing geothermal power plant, Tibet, China - Guo, Qinghai; Wang, Yanxin; Liu, Wei (Environmental earth sciences, 2008)
Thermal waters from the Yangbajing geothermal field, Tibet, contain high concentrations of B, As, and F, up to 119, 5.7 and 19.6 mg/L, respectively. In this paper, the distribution of B, As, and F in the aquatic environment at Yangbajing was surveyed. The results show that most river water samples collected downstream of the Zangbo River have comparatively higher concentrations of B, As, and F (up to 3.82, 0.27 and 1.85 mg/L, respectively), indicating that the wastewater discharge of the geothermal power plant at Yangbajing has resulted in B, As, and F contamination in the river. Although the concentrations of B, As, and F of the Zangbo river waters decline downstream of the wastewater discharge site due to dilution effect and sorption onto bottom sediments, the sample from the conjunction of the Zangbo River and the Yangbajing River has higher contents of B, As, and F as compared with their predicted values obtained using our regression analysis models. The differences between actual and calculated contents of B, As, and F can be attributed to the contribution from upstream of the Yangbajing River. Water quality deterioration of the river has induced health problems among dwellers living in and downstream of Yangbajing. Effective measures, such as decontamination of wastewater and reinjection into the geothermal field, should be taken to protect the environment at Yangbajing.